Emotion dynamics. (October 2017) - Kuppens, Peter; Verduyn, Philippe
Highlights: Reviews literature on emotion dynamics, the patterns of emotion change over time. Proposes a set of basic principles involved in emotion dynamics. Special attention goes to the role of emotion dynamics in psychological well-being. Abstract : The study of emotion dynamics involves the study of the trajectories, patterns, and regularities with which emotions (or rather, the experiential, physiological, and behavioral elements that constitute an emotion) fluctuate across time, their underlying processes, and downstream consequences. Here, we formulate some of the basic principles underlying emotional change over time, discuss methods to study emotion dynamics, their relevance for psychological well-being, and a number of challenges and opportunities for the future.